Biografi dan Pemikiran Pendidikan Ibnu Qayyim al-Jauziyyah: Analisis Relevansi terhadap Pendidikan Kontemporer - Shodiq, Arsyad; Tamyiz, Achmad; Masruroh, Masruroh; Khoir, Mulyanto Abdulloh (TSAQOFAH, 2026)
As one of the central figures in the history of Islamic thought, Ibn Qayyim al-Jawziyyah offers an integral educational vision that is regarded as relevant for addressing contemporary educational challenges, particularly in the midst of moral crises and the dualism between religious and general education. This study aimed to explore in depth the intellectual biography of Ibn Qayyim al-Jawziyyah and to analyse his educational thought in relation to its relevance to current educational challenges. A qualitative method with a library research approach was employed, using primary data derived from Ibn Qayyim’s fundamental works and secondary data from relevant supporting literature. The findings show that Ibn Qayyim’s intellectual journey, which was strongly influenced by Shaykh al-Islam Ibn Taymiyyah, shaped an educational framework grounded in the purification of the soul (tazkiyatun nufus) and the integration of revelation (wahyu) and reason. In his view, education simultaneously encompasses the dimensions of faith, morality, intellect, and physical development. Further analysis affirms that Ibn Qayyim’s educational thought remains relevant to contemporary educational contexts, especially through its emphasis on character education, the role of educators as exemplars, and an educational orientation that does not focus solely on cognitive intelligence but also on spiritual balance. This paper concludes that Ibn Qayyim’s concept of education can be positioned as an alternative point of reference for responding to moral crises and educational dualism in the modern era.